Neonatal Abandonment and Hydrocephalus in Antillean Manatees (Trichechus manatus manatus): Is There a Causal Relationship? - Tiago F. S. Santos; Márcio A. O. Moura; Gabriel S. F. Tavares; Julyanne S. Siqueira; Natália M. F. P. Sarmento; Robert G. S. Prado; Alexandra F. Costa; Tayanna M. M. M. Amaral; Renata Emin-Lima; Maura E. M. Sousa; Reginaldo H. M. Moreira Júnior; Pedro S. Bezerra Júnior; et al. (Animals)
Manatees are semi-social animals, with the mother–calf relationship being considered long-lasting for the species. However, some events lead to the separation of this pair. Orphaned manatee calves can be adopted by other females of the same species. However, if this does not happen and a healthy calf strand is rescued, immediate release represents the best option for the individual. But when immediate release becomes unviable, the animals are taken to rehabilitation centers and can die from various causes. A newborn Antillean manatee was rescued in the north of Brazil, and the attempt at immediate release was unsuccessful; three months later, the animal died. At necropsy, it was observed that the brain was soft and friable, collapsing when placed on a surface, with the corpus callosum region able to be ruptured easily and the cerebral hemispheres lying flaccid. The analysis of serial sections of the brain showed dilated lateral ventricles and a reduction in white matter, making it possible to affirm the presence of congenital hydrocephalus, the main factor that may have led to the abandonment of the offspring.